Melanoma risk during immunomodulating treatment. Issue 6 (22nd August 2022) - Zheng, Yixuan James; Ho, Wilson; Sanlorenzo, Martina; Vujic, Igor; Daud, Adil; Algazi, Alain; Rappersberger, Klemens; Ortiz-Urda, Susana
Abstract : Immunosuppressive therapy is standard for the treatment of inflammatory diseases and for minimizing rejection in transplant patients. However, immunosuppressant drugs are associated with an increased risk of certain cancers. In particular, melanoma is an immunogenic tumor and as such, is strongly influenced by the immune system. We performed this literature review to summarize the effects of commonly used immunomodulating agents on melanoma development, recurrence and progression. We outline the mechanism of action of each drug and discuss the available evidence on its influence on melanoma. Based on existing literature, we recommend avoiding the following agents in patients with a history of invasive melanoma: cyclosporine, sirolimus, natalizumab, IL-6 inhibitors, cyclophosphamide, methotrexate and the tumor necrosis factor-alpha inhibitors infliximab and etanercept. If there are no viable alternative agents, we recommend for these patients to see a dermatologist every 6 months for a thorough skin examination.